KAJIAN TEKNIS KEGIATAN PELEDAKAN DI PT. SEMEN BOSOWA MAROS SULAWESI SELATAN - Bambang Triyanto; Risanto Panjaitan (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
Drilling and blasting activities in PT. Semen Bosowa Maros quarry aims to dismantling limestones of the host rock with fragmentation expected size of ≤100 cm, considered the maximum size of rock crusher receive opening. The drilling pattern used is staggered pattern, while blasting pattern used is blasting streak pattern, with ignition of one line and straight lines of the one between next line. Based on observations in the field, the boulder that came from the blasting activities are relatively high at 20.63 %. To reduce the resulting chunks of the rock blasting activity, it’s important to change the geometry of blasting base formulation expressed by R. L. Ash, thus changes the distance to 3.1 m; spacing to 3.7 m; stemming height to 3.14 m; bench height to 5.80 m and depth of blasting hole to 6.10 m. With the new blasting geometry, lump sized rocks >100 cm generated from operating activities actual blasting theoretical calculations amounting only 14.82 %.